Students’ Strategies in Overcoming Problem in Speaking English - Tetin lamusu; Basalama, Nonny; Bay, Indri Wirahmi (Kirana Publisher (KNPub), 2025)
This research seeks to examine the challenges students encounter in speaking English and the strategies they employ to cope with them. The study applied a qualitative design, utilizing semi-structured interviews and thematic analysis with 15 students in their fourth semester of the English Language Education Study Program at Gorontalo State University. Results showed that learners experienced three major categories of speaking challenges: linguistic barriers (including limited vocabulary, mispronunciation, grammatical mistakes, and weak comprehension), psychological barriers (such as anxiety, lack of self-confidence, shyness, and low motivation), and social-environmental barriers (like insufficient peer support and limited exposure to English). To overcome these obstacles, students made use of several strategies, such as practicing independently, watching English-based content, engaging in peer conversations, boosting their learning motivation, and applying affective as well as social techniques. The outcomes of this study offer important insights for teachers and curriculum designers in fostering a classroom environment that enhances students’ English-speaking proficiency.